LEVEL OF UNDERSTANDING OF THE RIGHTS OF WORKERS/WOMEN WORKERS IN THE LABOR LAW AND ITS IMPLEMENTING REGULATIONS IN KLAMBIR LIMA KEBUN VILLAGE, HAMPARAN PERAK DISTRICT - Rika Jamin Marbun; Rahmayanti; Cut Ade Irma Handayani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the level of understanding of women's workers/laborers of their rights in the Manpower Law and its implementing regulations in Klambir Lima Kebun Village, Hamparan Perak District. The rights of women workers, such as the right to equal pay, social security, menstrual leave, maternity leave, and protection against discrimination, are an important part of legal protection for women workers. This study uses a quantitative approach with a descriptive design. The data was collected through a questionnaire distributed to women workers in the village. The results of the study showed that the majority of female workers in Klambir Lima Kebun Village have a limited understanding of their rights in the Labor Law and its implementing regulations. Many women workers are not fully aware of the rights protected by the law, whether in terms of fair wages, protection of working conditions, and the right to social security. Education on labor rights is expected to increase the understanding and awareness of women workers, so that they can optimize the legal protection that has been provided. This research is expected to provide recommendations for related parties to expand socialization and training programs on the rights of women workers at the village level, in order to improve the welfare and protection of women workers.